Effect of Mosaccha inoculum on fungal and yeast populations, sensory attributes, antioxidant activity, and ?-glucan content in cowpea tempeh - SAMSUL RIZAL; MARIA ERNA KUSTYAWATI; SUSSI ASTUTI; DITA ARTHA RISTIANI; FATIMAH FATIMAH; LIA DAHLIANI PRATIWI; RAHMAT HIDAYAT (Society for Indonesian Biodiversity, 2025)
Abstract. Rizal S, Kustyawati ME, Astuti S, Ristiani DA, Fatimah, Pratiwi LD, Hidayat R. 2025. Influence of Mosaccha inoculum on fungal and yeast populations, sensory profile, antioxidant level, and ?-glucan content of cowpea tempeh. Biodiversitas 26: 2926-2935. In addition to soybeans, cowpeas can also be used to make tempeh. Rhizopus oligosporus is the main fungus for fermentation, but the addition of Saccharomyces cerevisiae enhances the product's sensory qualities. This study aimed to evaluate the effects of Mosaccha inoculum, which combines R. oligosporus and S. cerevisiae, on the microbial, sensory, and chemical properties of cowpea tempeh. The experiment was conducted in a Complete Randomized Block Design (CRBD) with six inoculum concentrations (0.3%, 0.6%, 0.9%, 1.2%, 1.5%, and a control group with 0.2% Raprima inoculum), each replicated four times. Statistical analysis was done using Bartlett and Turkey tests, followed by ANOVA and LSD at a 5% significance level. The results indicated that the concentration of Mosaccha inoculum significantly influenced both fungal and yeast counts, as well as the sensory properties of the cowpea tempeh. The optimal inoculum concentration of 1.2% produced the highest quality tempeh, with a fungal count of 8.747 CFU/g and a yeast count of 8.570 CFU/g. The best sensory attributes included a white color with fully covered mycelium, a characteristic sweet aroma, a firm and easily sliced texture, and a taste that was well-accepted by panelists. The highest-quality Mosaccha cowpea tempeh meets the Indonesian National Standards for tempeh, contains 1.065% ?-glucan, and has an antioxidant level of 60.74%. These findings suggest that Mosaccha inoculum at 1.2% is an effective starter culture for producing high-quality functional cowpea tempeh. Its application offers an alternative to soybean-based tempeh while enhancing sensory and nutritional profiles. This innovation may support tempeh diversification using locally available legumes.